Os juízos de admissibilidade, rescindente e rescisório da ação rescisória: uma abordagem a partir da ponderação dos princípios da segurança jurídica e acesso à justiça - Medeiros, Maria Lúcia Lins Conceição de (2008)
The action seeking rescission is the remedy by means of which the material thing judged may be annulled. Because the thing judged is an institution expressly provided in the Brazilian constitutional text, in its art. 5, item XXXVI, the interpretation that is usually given to the rules under the constitution, which govern the action seeking rescission, is restrictive and focused on the prevailing idea of the juridical security, seen as a sub-principle of the Democratic Rule of Law. The reality is that the access to justice, which is also a sub-principle of the Democratic Rule of Law, was given a new dimension with the enactment of the 1988 Brazilian Constitution, and both its meaning and scope were broadened. In this context the access to justice was no longer seen merely as the right to request provision of the judicial protection. Its content became more comprehensive, involving the right to obtain the effective and efficacious juridical protection, which puts the two perspectives closer: the one of the reality established as a result of the lawsuit and the other consequent of the material right. In summary, the access to justice comprises the right to obtain a decision on the grounds of Law. By becoming aware of the particulars of the actual case, the judge is expected to find, in the general and abstract rule, a solution that conforms to the constitutional provisions and principles, as well as to the Fundamental Rights. The rescission action, provided that the admissibility requirements are met, is a second opportunity to make feasible the accomplishment of such goal. Based on such premise and seeking to make compatible the values at stake (namely, on one side, the thing judged and the stability that it inspires and, on the other side, the access to justice and the trust of the person under judicial protection that the Law will be enforced), this paper seeks to give suggestions based on doctrine and jurisprudence for a more flexible interpretation of the rules below the constitution, which govern the rescission action in the civil procedural system both with respect to the judgment of admissibility, and to the judgments making the previous judgment null (rescindente) and handing down a new decision on the action (rescisório), so that the rescission action of independent impugnation may serve its relevant role in the Democratic Rule of Law